Alterations to arbuscular mycorrhizal fungal community composition is driven by warming at specific elevations - Mei Yang; Zhaoyong Shi; Bede S. Mickan; Mengge Zhang; Libing Cao (PeerJ, 2021)
Background Global warming can alter plant productivity, and community composition which has consequences for soil-plant associated microorganisms. Arbuscular mycorrhizal fungi (AMF) are distributed widely and form symbiotic relationships with more than 80% of vascular plants and play a key role in nutrient cycling processes at the ecosystem scale. Methods A simulated warming experiment at multiple elevations (3,000, 3,500, 3,800, and 4,170 m) was conducted utilizing an in-situ open-top chamber (OTC) for exploring the effect of global warming on AMF community structure in the Qinghai-Tibet Plateau (QTP). This region has been identified as one of the most sensitive areas to climatic changes. Soil DNA was extracted and sequenced using next the Mi-Seq platform for diversity profiling. Results AMF richness was higher under the simulated warming chamber, however this only occurred in the elevation of 3,500 m. Warming did not alter other AMF alpha diversity indices (e.g. Shannon, Ace, and Simpson evenness index). Glomus and Acaulospora were the dominate AMF genera as assessed through their relative abundance and occurrence in control and warming treatments at the different elevations. Conclusion Warming changed significantly AMF community. The effects of warming on AMF community structure varied depend on elevations. Moreover, the occurrences of AMF in different genera were also presented the different responses to warming in four elevations.